Key Principles of Learning - Wulan Akhyari; Ahlunnazar; Asnuddin; Saprin (al-Afkar, Journal For Islamic Studies, 2025)
Education is a fundamental element in shaping human character and personality. One of the key aspects in education is the learning process, which is often the main focus but has not yet fully touched on the essence of the expected goals. Undirected learning tends to produce low quality. Therefore, learning principles are needed to serve as guidelines for teachers, especially in designing effective learning processes, including in Islamic Religious Education (PAI). The research method used is literature research by analyzing related literature to gain insight into the basic principles of the teaching profession. The results show that the application of these principles is very important in creating meaningful and effective learning, as well as being able to prepare students to face real life challenges. This research highlights learning principles that PAI teachers can apply, such as demonstration, application, task-centered, activation, and integration, as well as their relevance in a holistic learning process. These principles are designed to relate theory to real practice in learners' daily lives. With this approach, learning includes not only cognitive knowledge, but also spiritual skills and values, which are integrated through applicable and collaborative activities.